RELEVANSI KONSEP PENDIDIKAN TARBIYAH PERSPEKTIF M. YUSUF QARDHAWI DI ERA MODERN - Olga Yosnita Sari; Wedra Aprison (CV. ADIBA AISHA AMIRA, 2025)
This study examines how the concept of Tarbiyah education from the perspective of M. Yusuf Qardhawi affects today's world. Tarbiyah education, which emphasizes character building and moral principles, has great potential to be applied in modern education that is faced with many challenges, such as technological advancement and globalization. This research investigates Qardhawi's thoughts on holistic and integrative education. It also investigates how these principles can be applied in today's school curriculum. The research shows that Qardhawi's concept of education is not only relevant, but also essential for forming an intelligent and morally strong generation. In addition, the research found challenges and opportunities in the implementation of Tarbiyah education, and also provided suggestions on how Islamic values can be incorporated into contemporary education. Consequently, this study is expected to contribute to the development of an educational system that is more in line with the demands of the times and strong moral principles.